Diet induced obesity is independent of metabolic endotoxemia and TLR4 signalling, but markedly increases hypothalamic expression of the acute phase protein, SerpinA3N. Issue 1 (December 2018) - Dalby, Matthew; Aviello, Gabriella; Ross, Alexander; Walker, Alan; Barrett, Perry; Morgan, Peter
Abstract Hypothalamic inflammation is thought to contribute to obesity. One potential mechanism is via gut microbiota derived bacterial lipopolysaccharide (LPS) entering into the circulation and activation of Toll-like receptor-4. This is called metabolic endotoxemia. Another potential mechanism is systemic inflammation arising from sustained exposure to high-fat diet (HFD) over more than 12 weeks. In this study we show that mice fed HFD over 8 weeks become obese and show elevated plasma LPS binding protein, yet body weight gain and adiposity is not attenuated in mice lackingTlr4 or its co-receptorCd14 . In addition, caecal microbiota composition remained unchanged by diet. Exposure of mice to HFD over a more prolonged period (20 weeks) to drive systemic inflammation also caused obesity. RNAseq used to assess hypothalamic inflammation in these mice showed increased hypothalamic expression ofSerpina3n andSocs3 in response to HFD, with few other genes altered.In situ hybridisation confirmed increasedSerpina3n andSocs3 expression in the ARC and DMH at 20-weeks, but also at 8-weeks and increased SerpinA3N protein could be detected as early as 1 week on HFD. Overall these data show lack of hypothalamic inflammation in response to HFD and that metabolic endotoxemia does not link HFD to obesity.